2022
DOI: 10.1111/ene.15511
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of central nervous system involvement in Whipple's disease

Abstract: Background and purposeTo assess the clinical spectrum of central nervous system (CNS) involvement as well as cerebrospinal fluid (CSF) and neuroimaging findings in patients with Whipple's disease (WD) and to analyze the association of neurological symptoms with CSF and imaging findings.MethodsNeurological involvement was retrospectively analyzed in a series of 36 patients diagnosed with WD at a single center between 1992 and 2019. Findings of 81 comprehensive CSF examinations from 36 patients, including polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Foreign literature [4,7] reported that nervous system involvement in WD usually occurs after gastrointestinal symptoms and/or other systemic symptoms, usually with insidious onset and slow progress, and some patients may deteriorate suddenly. Approximately 80% of WD with CNS involvement is accompanied by involvement of other systems.…”
Section: Discussionmentioning
confidence: 99%
“…Foreign literature [4,7] reported that nervous system involvement in WD usually occurs after gastrointestinal symptoms and/or other systemic symptoms, usually with insidious onset and slow progress, and some patients may deteriorate suddenly. Approximately 80% of WD with CNS involvement is accompanied by involvement of other systems.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of neurological involvement is 6%-63% [ 1 - 3 , 6 ], presenting with confusion or coma due to meningoencephalitis or status epilepticus, cognitive impairment with memory loss and attention deficit, pyramidal, and extrapyramidal symptoms, sleep disorders, cerebellar palsy, abnormal involuntary movements (including oculomasticatory or oculofacial-skeletal myorhythmia), oculomotor nerve palsy and progressive dementia [ 7 ]. Analysis of CSF reveals normal cytology in around half of the patients with neurological symptoms, with the remainder of cases having a CSF compatible with lymphocytic meningitis, with normal or high protein levels [ 7 , 8 , 10 ]. Despite this, detection of T. whipplei through PCR seems to be as high as 41%-63% of all cases of classic WD who underwent lumbar punction, even without neurological symptoms [ 2 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of CSF reveals normal cytology in around half of the patients with neurological symptoms, with the remainder of cases having a CSF compatible with lymphocytic meningitis, with normal or high protein levels [ 7 , 8 , 10 ]. Despite this, detection of T. whipplei through PCR seems to be as high as 41%-63% of all cases of classic WD who underwent lumbar punction, even without neurological symptoms [ 2 , 10 , 11 ]. If neurologic symptoms are present, up to 59.1%-92% have a positive PCR for T. whipplei [ 2 , 7 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations